Visual and multimodal urban sociology. part A : imagining the sensory city - Pauwels, Luc (Research in urban sociology ;, 2023)
More extensive methodology is required to study the complexities of everyday life in the rapidly expanding urban areas around the globe, as well as to gain a better understanding of life in established urban areas. Presented over two volumes, Visual and Multimodal Urban Sociology A and B explore the use and potential of visual materials and methodologies that expand the level of analysis and ways of seeing in urban sociology. Both volumes comprise examinations of sources, tools, and methods to capture, analyze, and communicate the visual dimension of urban environments, using existing visual sources as well as visual media as tools to both produce data and communicate insights and views on the contemporary urban condition and experience. Visual and Multimodal Urban Sociology Part A imagines the sensory city through cross disciplinary perspectives, methods, and technology, considering the city as home, the past as a data visualization and analysis tool, geo-referencing and historic photographs, playing the Early Renaissance City, and concluding with learning from street view. Yielding empirical data and insights regarding the visually observable impact of urban planners, designers, advertisers, commercial forces, cultural institutions, local authorities, artists, protesters as social agents in the (re)production of urban cultural processes, both volumes are a novel and wide-ranging contribution that advances the contours and potential of a more 'visual' urban sociology.